The Novel Role of Metabolism-Associated Molecular Patterns in Sepsis - Zhu, Xin-xu; Zhang, Wen-wu; Wu, Cheng-hua; Wang, Shun-shun; Smith, Fang Gao; Jin, Sheng-wei; Zhang, Pu-hong (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis, a life-threatening organ dysfunction, is not caused by direct damage of pathogens and their toxins, but the host's severe immune and metabolic dysfunction caused by the damage when the host confronts against infection. Previous views focused on the Damage-associated molecular patterns (DAMPs) and Pathogen-associated molecular patterns (PAMPs), included metabolic pro-inflammatory factors in sepsis. Recently, new concepts have been proposed to group free fatty acids (FFAs), glucose, advanced glycation end products (AGEs), cholesterol, mitochondrial DNA (mtDNA), oxidized phospholipids (OxPLs), ceramides, and uric acid into Metabolism-Associated Molecular Patterns (MAMPs). The concept of MAMPs will bring a new guidance to the research and potential treatments of sepsis. Nowadays, sepsis is regarded as closely related to metabolic disorders, and MAMPs play an important role in the pathogenesis and development for sepsis. According to this view, we have explained MAMPs and their possible roles in the pathogenesis of sepsis. Next, we have further explained the specific functions of different types of MAMPs in the metabolic process and their interactional relationship with sepsis. Finally, therapeutic prospects of MAMPs in sepsis have been summarized.